Analisis Kegunaaan dan Kemudahan Sistem Teknologi pada Aplikasi Mobile Banking terhadap Keamanan Bertransaksi Non Tunai di Kalangan Mahasiswa - Prasetyo, Angga Dwi; Nuraini; Lubis, Riska Amelia; Nurbaiti (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The development of banking services not only aims for security and reliability, but also to provide services that are adapted to technological developments and needs, as mobile banking involves combining information technology and business applications together Mobile Banking is a banking service provided by the bank to support the smoothness, convenience and security for the use of banking activities in terms of customer effectiveness and efficiency in transactions. This study aims to determine the ease of use of the Mobile Banking technology system for non-cash transactions among students. The approach used in this research is a qualitative approach by going to the field, namely interviews with respondents of 5C class Islamic Banking students. The research method is based on the philosophy of the key instrument and also produces written or oral data. The usefulness and convenience obtained from mobile banking on security in non-cash transactions provides significant results and benefits in non-cash transaction problems among students because it is very efficient and helpful. In addition, the security side of the transaction must also be considered so that nothing unwanted happens.